Bone formation around unstable implants is enhanced by a WNT protein therapeutic in a preclinical in vivo model - Coyac, Benjamin R. (Clin Oral Implants Res, 2020)
OBJECTIVES: Our objective was to test the hypothesis that local delivery of a WNT protein therapeutic would support osseointegration of an unstable implant placed into an oversized osteotomy and subjected to functional loading. MATERIALS AND METHODS: Using a split-mouth design in an ovariectomized (OVX) rat model, 50 titanium implants were placed in oversized osteotomies. Implants were subjected to functional loading. One-half of the implants were treated with a liposomal formulation of WNT3A protein (L-WNT3A); the other half received an identical liposomal formulation containing phosphate buffered saline (PBS). Finite element modeling estimated peri-implant strains caused by functional loading. Histological, molecular, cellular, and quantitative micro-computed tomographic (μCT) imaging analyses were performed on samples from post-implant days (PID) 3, 7, and 14. Lateral implant stability was quantified at PID7 and 14. RESULTS: Finite element analyses predicted levels of peri-implant strains incompatible with new bone formation. Micro-CT imaging, histological, and quantitative immunohistochemical (IHC) analyses confirmed that PBS-treated implants underwent fibrous encapsulation. In those cases where the peri-implant environment was treated with L-WNT3A, μCT imaging, histological, and quantitative IHC analyses demonstrated a significant increase in expression of proliferative (PCNA) and osteogenic (Runx2, Osterix) markers. One week after L-WNT3A treatment, new bone formation was evident and two weeks later, L-WNT3A treated gaps had a stiffer interface compared to PBS-treated gaps. CONCLUSION: In a rat model, unstable implants undergo fibrous encapsulation. If the same unstable implants are treated with L-WNT3A at the time of placement, then it results in significantly more peri-implant bone and greater interfacial stiffness.